Mantle Cell Lymphoma in the Thyroid: A Rare Presentation - Uzma Mohammad Siddiqui; Sarika N. Rao; Pallavi Kanwar Galera; Nahida Islam; Mira S. Torres (Case Reports in Pathology)
Background. While 2% of all extranodal Non-Hodgkin Lymphomas present in the thyroid, there exists insufficient data to describe the incidence of mantle cell lymphoma in the thyroid. A case series of 1400 patients revealed that <1% of thyroid lymphomas may be MCL; hence better understanding of the disease course is essential. Patient Findings. A 65-year-old female was referred for a multinodular goiter. Multiple fine needle aspirations from the dominant right nodule were consistent with Hashimoto’s thyroiditis and flow cytometry was negative. Due to progressing dysphagia, she underwent total thyroidectomy. Summary. Pathology revealed MCL with mantle zone growth pattern in the right thyroid. Flow cytometry showed monoclonal B cells comprising 9% of total cells. The Ki-67 index was 10%. She was diagnosed as having stage IIE MCL and offered conservative management by medical oncology, given that she had no B symptoms. Conclusion. Though chemotherapy is the treatment of choice in MCL, a subset of patients with low-grade disease may be observed. As in our patient, mantle zone growth pattern and a Ki-67 index < 10% suggest a favorable prognosis. A diagnosis of primary MCL in the thyroid remains rare and staging modalities as well as treatment options continue to evolve.